Teritorialitas Ruang pada Jalur Pedestrian Kawasan Bisnis Cakranegara, Kota Mataram - Ni Ketut Ayu Intan Putri Mentari Indriani (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2023)
Pedestrian Ways are one of the city elements that consist of public open spaces as a container for activities and pedestrian circulation. The existence of pedestrian ways is very important to support urban activities, so the effectiveness of the function of Pedestrian Ways also needs to be considered. The study area is located on the corridor of Jl. A.A. Gede Ngurah, which is part of the Cakranegara Business District (CBD) and known as the center of the business district of Mataram City, so the potential for mobility and pedestrian activities is quite high. Unfortunately, this potential is not supported by the spatial behavior of the community, which tends to form certain spatial claims on pedestrian ways, resulting in a disruption of space function. This research was conducted to determine how the phenomenon of public space claims is formed in the study area. The research method used was a qualitative descriptive method with observation techniques to observe the phenomenon that occurred in the field. In general, from the results of the research, it can be concluded that the spatial claims of the surrounding community in the study area lead to territorial behavior with territorial expansion patterns and privatization of public space for personal interests.